Aprendizagem cooperativa em aulas de química: análise da correlação entre desempenho acadêmico e cooperativo versus responsabilidade individual e interação promotora na escola estadual de educação profissional Alan Pinho Tabosa em Pentecoste-CE - Sousa, Francisco Milton de (2015)
If education is more than teaching school subjects, the success of this education should not be evaluated considering only the marks awarded through assessments of knowledge on such content. There is therefore a need to establish evaluative strategies that are capable of contemplating other non-cognitive skills,which are expected to be developed by the students during their education. In addition, it is extremely important that students are informed about their performance in these assessments so that they can feel that these skills are valued by the school. When it only evaluates the academic performance of students, it means that only this kind of performance has value to school. In schools where only the academic achievement is valued, students who do not excel in this criterion, even if they have the ability to put yourself in the other, get along and share what you know with your colleagues being able to practice cooperation, never win medals or at least are called "good student". This research work conducted an educational intervention in school to consolidate a systematic approach student academic achievement assessment and at the same time, of their cooperative potential. In addition to this assessment approach, the research aimed to show that the individual responsibility and promoting interaction level affects the academic and cooperative student performance and that these, feel more encouraged to cooperate with each other when they receive frequent feedback regarding your cooperative performance in the classroom. The research was divided into two phases, and each of them, there were four classes using cooperative learning, which addressed eight objects of knowledge relating to chemistry curriculum of the fourth quarter of the 1st year of high school. Data were obtained through partial and global knowledge assessments and through a research questionnaire at the end of each lesson. The results showed that the courses in which students demonstrated their greater individual responsibility and greater interaction promoter, were considered most cooperatives and had higher academic achievement. The data analysis also allowed to infer that all classes have improved academic and cooperative performance in the 2nd phase of the research, after students receive teacher feedback on their cooperative performance. The study was conducted at the State School of Professional Education (EEEP) Alan PinhoTabosa, in the municipality of Pentecoste-CE, educational institution that already use cooperative learning in a systematic way, in all their classes and subjects, from the year 2012.